Neuropathological features of levodopa-responsive parkinsonism in multiple system atrophy: an autopsy case report and comparative neuropathological study - Tamura, Mitsuyoshi; Takeda, Takahiro; Kitayama, Yoshihisa; Suichi, Tomoki; Shibuya, Kazumoto; Harada-Kagitani, Sakurako; Kishimoto, Takashi; Kuwabara, Satoshi; Hirano, Shigeki (Frontiers in Neurology, 2023)
BACKGROUND: In typical patients with multiple system atrophy with predominant parkinsonism (MSA-P) levodopa is ineffective. However, there are some of these patients who respond well to levodopa treatment. Levodopa efficacy in MSA-P patients is thought to be related to the degree of putaminal damage, but the pathological causation between the putaminal involvement and levodopa efficacy these two has not been established in detailyet.OBJECTIVE: This study aimed to evaluate the neuropathological features of the nigrostriatal dopaminergic system in a "levodopa-responsive" MSA-P patient in comparison with "levodopa-unresponsive" conventional MSA-P patients.MATERIALS AND METHODS: Clinicopathological findings were assessed in a 53-year-old Japanese man with MSA who presented with asymmetric parkinsonism, levodopa response, and later wearing-off phenomenon. During autopsy, the nigrostriatal pathology of presynaptic and postsynaptic dopaminergic receptor densityfunctions and α-synuclein status were investigated. The other two patients with MSA-P were examined using the same pathological protocol.RESULTS: Four years after the onset, the patient died of sudden cardiopulmonary arrest. On autopsy, numerous α-synuclein-positive glial cytoplasmic inclusions in the basal ganglia, pons, and cerebellum were identified. The number of neurons in the putamen and immunoreactivity for dopamine receptors were well-preserved. In contrast, significant neuronal loss and decreased dopamine receptor immunoreactivity in the putamen were observed in the "levodopa-unresponsive" other two MSA-P control patients. These putaminal pathology results were consistent with the findings of premortem magnetic resonance imaging (MRI). All three patients similarly exhibited severe neuronal loss in the substantia nigra and decreased immunoreactivity for dopamine transporter. CONCLUSIONS: Levodopa responsiveness in patients with MSA-P may be corroborated by Tamura et al., P3 3 the normal putamen on MRI and the preserved postsynaptic nigrostriatal dopaminergic system on pathological examination. The results presented in this study may provide a rationale for continuation of levodopa treatment in patients diagnosed with MSA-P.